Using the Edinburgh Postnatal Depression Scale to achieve best practice standards - Downie, Jill; Wynaden, Dianne; McGowan, S.; Juliff, D.; Axten, C.; Fitzpatrick, L.; Ogilvie, S.; Painter, S. (Blackwell Synergy, 2003)
The present paper reports the findings of a quantitative descriptive study that evaluated the use of the Edinburgh Postnatal Depression Scale (EPDS) as a screening tool in the child health context. Two hundred and sixty-one women who attended child health clinics in one metropolitan health region of Western Australia over a designated 4-week period for a 6 8 week or 7 9 month health scheduled infant screening assessment agreed to participate. The study aimed to (i) identify the proportion of women in the study who scored 13 or greater on the EPDS; (ii) evaluate current practice outcomes from the use of the EPDS by child health nurses and; (iii) report demographic variables associated with scores obtained from participants. Findings showed that the EPDS is a useful screening tool to identify women who may be at risk of developing depression during the postpartum period. However, the study also identified a weakness in clinical practice protocols, with some child health nurses not referring women who reported symptoms of depression on the self-report scale. Therefore, to ensure best practice standards more education regarding clinical practice protocols needs to be implemented with child health nurses in order to facilitate optimal outcomes for women using the self-report scale